Sustainability and Halal tourism: Convergence of ethical, environmental, and religious values - Muharis Muharis; Muhammad Taufik; Muhammad Alam Setiawan (Priviet Social Sciences Journal, 2026)
This study explores the link between halal tourism and the Sustainable Development Goals (SDGs) and identifies its contribution to developing ethical, inclusive, and sustainable tourism destinations. This study was compiled using a Systematic Literature Review (SLR) method with the PRISMA 2020 approach, encompassing 42 selected scientific articles that met the quality and relevance criteria. Data were collected through a systematic search process in the Scopus database, screening based on titles and abstracts, and article quality evaluation. The study's findings indicate that halal tourism not only meets the spiritual needs of Muslim tourists but also contributes to local economic empowerment, environmental preservation, and strengthening cultural identity. Islamic values such as justice, responsibility, and sustainability are important foundations for developing halal destinations that align with the principles of the SDGs. Furthermore, local community participation, the use of digital technology, and a contextual branding approach contribute to strengthening halal tourism’s competitiveness and sustainability. This study concludes that the integration of Sharia principles and global sustainability makes a significant contribution to the development of sustainable tourism theory and practice. Further studies are recommended to adopt a multidisciplinary approach, expand the scope of the region, and use a longitudinal design to deepen the understanding of the dynamics and challenges in this sector.